Impact of High-Performance Work Systems on Export-Oriented SMEs Performance: The Mediating Role of Human Capital Development - Hamid, Zeeshan (The South East Asian Journal of Management, 2017)
Small and medium enterprises (SMEs) contribute substantially to the economic development, income generation, poverty reduction, and particularly job creation for both developed and developing economies. However, compared with large firms, SMEs face several challenges related to their performance and competitiveness. The role of human capital (HC) and human resource practices (HR Practices) in enhancing SMEs competitiveness and performance is vital but understudied areas. Therefore, the purpose of this study was to investigate the role of HC development between the relationship of high-performance work systems (HPWS) and export-oriented SMEs performance. Quantitative strategy and cross-sectional survey method was used to collect data from 205 managerial staff through a self-administered structured questionnaire. HPWS had a significant positive impact on export-oriented SMEs performance. The findings of the study provide evidence that HC development plays a mediating role between HPWS and enterprises performance.